Loading necrostatin-1 composite bone cement inhibits necroptosis of bone tissue in rabbit. Issue 2 (4th February 2019) - Ji, Xiang; Xu, Feng; Dong, Guoling; Jia, Chongzhe; Jia, Pu; Chen, Hao; Tang, Hai
Abstract: Bone necrosis after injecting of polymethylmethacrylate (PMMA) bone cement will lead to re-fracture of bone tissue. As a new type of necrosis, there is little research related to the necroptosis of surrounding bone tissue near the bone cement. The purpose of our study was to (i) investigate the presence of necroptosis in vivo and, (ii) established as a new type of bone cement containing PMMA, calcium phosphate cement (CPC) and Necrostatin-1 (Nec-1) to inhibit necroptosis of bone tissue. A total of 12 Japanese rabbits were used to establish the animal model and randomly divided into 4 groups signed as a control group, PMMA group, PMMA–CPC group and PMMA–CPC–Nec-1 group, respectively. We used scanning electron microscope to observe the structure of the samples, used HE staining to detect the necrosis, and used western blotting as well as ELISA test to examine the iconic molecule receptor interacting protein kinase-3 (RIP 3) protein and tumor necrosis factor α (TNF-α). After analyzing the results of our study, we found that the structure in both PMMA bone cement group and composite bone cement group was damaged and there was an evidence of necrosis, but it was absent in control group. Through molecule detection, the RIP 3 protein expression was decreased in PMMA–CPC–Nec-1 ( P < 0.05). TNF-α expression was increased in bone cement groups with and without CPC ( P < 0.05), but was inhibited in PMMA–CPC–Nec-1 group. We have concluded that the necroptosis could be confirmed in bone tissue necrosis induced by TNF-α after bone cement injection and also could be inhibited by composite bone cement with Nec-1.